Why would individuals use indoor positioning systems? A study from a potential user interface perspective - Thomas Paetow; Johannes Wichmann; Michael Leyer (PLoS ONE, 2026)
Indoor positioning systems (IPS) differ from outdoor navigation in technological foundations and typical use cases, yet real-world deployments remain relatively rare. For an early-stage acceptance evaluation, literature-derived IPS functions were implemented as an interactive, task-based UI mock-up for a university setting. UTAUT2 was assessed with a pooled sample of 181 potential users across three independent data collections using PLS-SEM with one-tailed BCa bootstrap confidence intervals (90%; 5%/95% bounds). Performance expectancy showed the largest positive association with behavioral intention (β = 0.585, CI [0.480; 0.678]). Social influence (β = 0.179, CI [0.115; 0.245]), price value under a communicated one-time fee of €0.99 (β = 0.179, CI [0.096; 0.260]), and habit (β = 0.179, CI [0.097; 0.265]) also related positively to intention (R² = 0.781). Effort expectancy (β = −0.051, CI [−0.136; 0.023]), facilitating conditions (β = −0.027, CI [−0.108; 0.046]), and hedonic motivation (β = −0.002, CI [−0.109; 0.113]) were not supported; a robustness model indicated a negative age × price value interaction (β = −0.164, CI [−0.314; −0.071]). The findings extend UTAUT2 evidence to prototype-based IPS UI evaluation and suggest that performance-related beliefs dominate early intention formation. Practically, prototype concepts should prioritize and clearly communicate features that reduce uncertainty, time cost, and search effort in complex indoor environments. Because the stimulus was a UI mock-up and the outcome was self-reported intention, IPS-specific technical frictions (e.g., localization inaccuracies, latency, route deviations) and sustained real-world use were not observed, which may limit transferability to deployed IPS.